Getek - Megat Junid Megat Ayob. ([Petaling Jaya : s.n., 2000)
Autobiography of Megat Junid bin Megat Ayob, Malaysia's Minister of Domestic Trade and Consumer Affairs.
Cover title.
In Malay.
Keywords: Megat Junid Megat Ayob; Cabinet officers -- Malaysia -- Biography